The Influence of Promotion and Sevice Facilities on Tourist Satisfaction on Punjabu Hill, Buntu Buangin Village, Pitu Riase District, Sidenreng Rappang Regency - Aidil Malik; Moh. Aris Pasigai; Syarthini Indrayani (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to determinne and analyze “The Influence of Promotion and service Facilities on Tourist Satisfaction at Punjabu Hil, Buntu Buangin Village, Pitu Riase District, Sidenreng Rappang Regency”. The type of research used is a quantitative method. The data quw=estionnaire. The data analysis method uses are validity testing, reliability testing, classical assumption testing, multiple linear regression testing and hypothesis testing using SPSS version 26 analysis tools. Based on the results of research that has been conducted, it shows that the influence of promotions and services facilities has a positive effect on tourist satififactio. On Punjabu Hill, Buntu Buangin Village, Pitu Riase District, Sidenreng Rappang Regency. This is indicated by the calculated t value of 4.544 which is greater than the t table of 1.659 with a determination test of 0.462 with a positive relationship.